PERAN GERAKAN PEREMPUAN DALAM PROSES INSTITUSIONALISASI NORMA KESETARAAN GENDER INTERNASIONAL - Setiyaningsih, Dewi (Universitas Widya Mataram, 2022)
This study aims at analyzing the role of women movement in Europe and US in creating gender equality norm. Using qualitative approach and life cycle of norm theory developed by Finnemore & Sikkink, this study tries to explain the development of gender equality norm through three stages, they are norm emergence, norm cascade and norm institutionaization. The result shows that there is the strong involvement of women movement in each stage, starts from the aftermath era until the modern era, when the internatioal organization such as Nation Leagues and United Nations are started to emerge. Step by step shows the women movement’s startegies in promoting gender equality norm to be institutionalized through international organization.